2014
DOI: 10.1002/chem.201403983
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Alkyne Alkoxycarbonylation at a Pd Catalyst with P,N Hemilabile Ligands: A Density Functional Study

Abstract: A detailed mechanism for alkyne alkoxycarbonylation mediated by a palladium catalyst has been characterised at the B3PW91-D3/PCM level of density functional theory (including bulk solvation and dispersion corrections). This transformation, investigated via the methoxycarbonylation of propyne, involves a uniquely dual role for the P,N hemilabile ligand acting co-catalytically as both an in situ base and proton relay coupled with a Pd(0) centre, allowing for surmountable barriers (highest ΔG(≠) of 22.9 kcal mol(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…We have already proposed a simple ligand modification that should lower the turnover-determining barrier, 51 and further studies along these lines are in progress.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…We have already proposed a simple ligand modification that should lower the turnover-determining barrier, 51 and further studies along these lines are in progress.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…A DFT study of the mechanism of the propyne methoxycarbonylation to produce methyl methacrylate, catalyzed by a Pd complex of 2-pyridyldiphenylphosphine ligand and methanesulphonic acid (MesOH) co-catalyst, has been recently reported [13]. This study proposes two steps where the hemilabile ability of the P,N-donor ligand plays a crucial and distinctive role.…”
Section: Resultsmentioning
confidence: 94%
“…For instance, Pd complexes with P,N-donor ligands are active in the reductive carbonylation of nitroaromatics [10] and CO-alkene polymerization [11,12], but the most important process of this type is undoubtedly the industrial carbonylation of alkynes to produce methyl methacrylate and related products catalyzed by a palladium complex of 2-diphenylphosphino-pyridine (Ph 2 Ppy), Fig. 1 [13]. Furthermore, a Pd(II) complex of 2-(diphenylphosphinoamino)-pyridine (Ph 2 PNHpy) is active in the carbonylation of ethanol to ethyl propionate [14].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] However, Gusev 22 recently stated that the continuing use of the B3LYP method may be related to a lack of confidence in the newer methods rather than its performance. Furthermore, Gusev demonstrated that the M06-L functional is a good quality and Fig.…”
Section: Theoretical Methodsmentioning
confidence: 96%